Analisis Pendekatan Metacognitive Guidance dalam Pembelajaran Matematika: Systematic Literature Review - Elyse Silvia Purba; I Gusti Putu Suharta; I Made Suarsana (CV. Alim's Publishing, 2026)
This study focuses on examining the effectiveness of the metacognitive guidance approach in mathematics education using the Systematic Literature Review (SLR) method. Metacognitive strategies are considered a relevant approach in 21st-century education because they encourage students to plan, monitor, and evaluate their thinking processes independently. The literature search was conducted via Google Scholar using appropriate keywords and yielded 306 articles in the initial stage. Subsequently, the selection process followed the PRISMA flowchart, including the removal of duplicate articles, screening based on titles and abstracts, and eligibility assessment through full-text review. From these stages, 12 articles meeting the inclusion criteria were selected as the basis for analysis. The study’s findings indicate that metacognitive guidance has a positive impact on mathematics learning, particularly on students’ problem-solving skills, critical thinking, mathematical literacy, and learning outcomes. This approach also enhances metacognitive awareness, enabling students to be more focused in selecting strategies, monitoring the learning process, and evaluating the results. Thus, this strategy is worthy of integration by teachers to strengthen the quality of learning and higher-order thinking skills.